Distribution of Safety Messages Using Mobility-Aware Multi-Hop Clustering in Vehicular Ad Hoc Network - Rajeshwari Chiluveru; Nishu Gupta; Ariel Soares Teles (Future Internet, 2021)
Reliability and security when distributing safety messages among vehicles in an extremely mobile environment are prominent issues in Vehicular Ad-Hoc Networks (VANETs). In VANET, data transfer becomes challenging because of inherent features such as excessive speed, geographically constrained topologies, unsteady communication links, diversity in the capacity of the channel, etc. A major challenge in the multi-hop framework is maintaining and building a path under such a rigid environment. With VANET, potency in the traffic safety applications has performed well because of the proper design of medium access control (MAC) protocols. In this article, a protocol is proposed pertaining to the distribution of safety messages named mobility-aware multi-hop clustering-based MAC (MAMC-MAC) to accomplish minimum communication overhead, high reliability, and delivery of safety messages in real-time environments. MAMC-MAC has the ability to establish clustering-based multi-hop sequence using the time-division multiple access (TDMA) technique. The protocol was specially developed for highway outlines to achieve network enhancement and efficient channel usage and guarantees integrity among the vehicles. The performance of the proposed protocol is evaluated using Network Simulator (NS-2), and it demonstrates its superiority over various standard protocols in terms of a number of quality-of-service (QoS)-based parameters. The criteria to select and assess these parameters are their sensitivity and importance to the safety-based applications they provide.